The Arrowhead Framework applied to Energy Management - Rocha, Rafael (2018)
Energy management in buildings can provide massive benefits in financial and energy saving terms. It is possible to optimize energy usage with smart grid techniques, where the benefits are enhanced when the energy consumer can trade the energy on energy markets, since it forces energy providers to compete with each other on the energy price. However, two hurdles oppose this approach: the devices providing control over appliances do not interoperate with each other; and energy markets limit trading activities to large quantities of energy, thus impeding access for small consumers. This work considers using the FlexOffer (FO) concept to allow the consumer to express its energy needs, and FO-related mechanisms to aggregate energy requests into quantities relevant for energy markets. Moreover, the presented system, named FlexHousing, is based on the Arrowhead Framework – a framework that simplifies design and implementation of distributed applications by means of normalizing communication via services – and exploits its Service Oriented mechanisms to provide device interoperability. The implemented FlexHousing system uses multi-level FO aggregation to empower either the final user, for example the owner of an apartment, to manage its own energy by defining their flexibilities, or to offload this responsibility to an energy manager who takes care of all the apartments in a building or set of buildings.